2007
DOI: 10.2174/138920007780866861
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Drug Interactions via Mechanism-Based Cytochrome P450 Inactivation: Points to Consider for Risk Assessment from In Vitro Data and Clinical Pharmacologic Evaluation

Abstract: This commentary discusses the approaches to, and key considerations in the in vitro-in vivo extrapolation of drug-drug interactions (DDI) resulting from mechanism-based inactivation (MBI) of cytochrome P450 (CYP) enzymes and clinical pharmacologic implications. In vitro kinetic assessment and prediction of DDI produced via reversible inhibition and MBI rely on operationally and conceptually distinct approaches. DDI risk assessment for inactivators requires estimation of maximal inactivation rate (k(inact)) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
61
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(62 citation statements)
references
References 78 publications
1
61
0
Order By: Relevance
“…For example, erlotinib and dasatinib are mechanism-based inactivators of CYP3A [15,16], a characteristic of many important inhibitors of drug metabolism [17,18]. Product information for these drugs indicates minor impact on the clearance of CYP3A substrates [Sprycel® (dasatinib), labelling,Tarceva® (erlotinib) labelling], but these data are not in the public domain.…”
Section: Discussionmentioning
confidence: 99%
“…For example, erlotinib and dasatinib are mechanism-based inactivators of CYP3A [15,16], a characteristic of many important inhibitors of drug metabolism [17,18]. Product information for these drugs indicates minor impact on the clearance of CYP3A substrates [Sprycel® (dasatinib), labelling,Tarceva® (erlotinib) labelling], but these data are not in the public domain.…”
Section: Discussionmentioning
confidence: 99%
“…Frequently, mathematical models are also used that enable scaling of these and other pertinent information into a quantitative prediction of the expected magnitude of DDI (typically expressed as an AUC ratio of the object in the presence and absence of the precipitant). Prior work has demonstrated that this approach can indeed yield accurate DDI predictions (Ito et al, 1998(Ito et al, , 2004Mayhew et al, 2000;Wang et al, 2004;Venkatakrishnan and Obach, 2007). However, to date, such quantitative approaches have not been comprehensive in that they assume a singular mechanism of action.…”
Section: Discussionmentioning
confidence: 99%
“…Many drug-drug interactions (DDIs) result from altering the activities of these enzymes. A considerable effort in the area of drug metabolism is dedicated toward predicting clinical pharmacokinetics and DDIs from in vitro data (Ito et al, 1998(Ito et al, , 2004Mayhew et al, 2000;Wang et al, 2004;Venkatakrishnan and Obach, 2007). The prediction of DDIs based on an assumption of reversible P450 inhibition has been a standard part of preclinical programs in the pharmaceutical industry for many years.…”
mentioning
confidence: 99%
“…A key parameter used in these models is the inhibitor concentration at the enzyme active site (I u ) (Mayhew et dmd.aspetjournals.org these concentrations cannot be directly measured, surrogates based on plasma levels are often used. Retrospective analysis has shown that C max or average plasma concentrations have been successfully used in predicting the magnitude of DDIs resulting from coadministered inhibitors (Brown et al, 2006;Galetin et al, 2006;Venkatakrishnan and Obach, 2007).…”
Section: Discussionmentioning
confidence: 99%